Bioaccumulation of lead (Pb) and its effects in plants: A review - Collin, Samuel; Baskar, Amritha; Geevarghese, Deepthi Mariam; Ali, Mohamed Niyaz Vellala Syed; Bahubali, Praveena; Choudhary, Rajan; Lvov, Vladislav; Tovar, Gabriel Ibrahin; Senatov, Fedor; Koppala, Sivasankar; Swamiappan, Sasikumar (Journal of hazardous materials letters, 2022)
Heavy metals (HM) toxicity is becoming a major threat to living organisms in recent years due to the increase in population and anthropogenic activities. Lead (Pb) shares about 10% of total pollution produced by heavy metals. The uptake of lead by the primary producers (plants) is found to affect their metabolic functions, growth, and photosynthetic activity. The accumulation of lead in excess can cause up to a 42% reduction in the growth of the roots. The current review addresses the global status of lead contamination in soil, potential lead sources, and the mechanism of lead uptake by the plants. This article also provides information about the lead concentration in plants in polluted and non-polluted areas. Humans are directly or indirectly dependent on plants to meet their daily requirements. So, it becomes necessary to review the problems associated with lead pollution in plants and its mode of action affecting the plant system. Factors like bioaccumulation, bioavailability, bioconcentration, transfer factor, and the role of Casparian strips as a natural physical barrier are discussed. Further, the updated literature survey about the various bioremediation strategies utilized for its elimination is also presented. The current study suggests that more attention needs to be focused on evaluating the effectiveness of bioremediation methods.